The effectiveness of Ovaprim with different concentrations on the duration of spawning and hatching power of goldfish eggs (Carassius auratus) - Rumondang, Anne; Huda, Muhammad Aidil; Yeni, Mutiaragusti (Acta Aquatica: Aquatic Sciences Journal, 2025)
This study aims to analyze the effectiveness of Ovaprim at various concentrations on spawning time, fertilization rate, and egg hatchability of goldfish. This study uses an experimental method with a Completely Randomized Design (CRD) consisting of four treatments: P1 (control/0 ml/kg), P2 (0.2 ml/kg), P3 (0.3 ml/kg), and P4 (0.4 ml/kg)/of fish body weight. Each treatment was repeated three times. The observed parameters in this study include spawning time, fertilization rate, and egg hatchability. The obtained data were analyzed using ANOVA and followed by Duncan's multiple range test to determine significant differences between treatments. The research results show that the use of Ovaprim at different concentrations has a significant effect on spawning time, fertilization rate, and hatching rate. The 0.4 ml/kg dose provided the best results, with the fastest spawning time of 10 hours and 3 minutes, a fertilization rate of 88.67%, and the highest hatching rate, reaching 93.30%. Thus, a dose of 0.4 ml/kg is recommended as the optimal dose to improve the spawning efficiency of goldfish in aquaculture. Keywords: Carassius auratus; Hatchability; Ovaprim; Reproductive Hormone; Spawning